INDENTIFIKASI KARATERISTIK KIMIA TANAH DAN EVALUASI STATUS KESUBURAN TANAH PADA LAHAN TANAMAN NANAS DI KELURAHAN WALAMBENO WITE KECAMATAN PARIGI KABUPATEN MUNA - Mpia, La; Hasbiadi, Hasbiadi; R, Mustafa; Handayani, Fitrianti (Fakultas Pertanian Universitas Mataram, 2023)
Soil fertility provides an overview of the condition of the soil to provide nutrients. As land management is carried out intensively and over a long period of time, a decrease in soil fertility occurs. The research objectives to identify the chemical characteristics of the soil and evaluate the level of fertility of the soil planted with pineapple plants. This research was carried out in Walambeno Wite Village, Parigi District, Muna Regency, Southeast Sulawesi Province. Walambeno Wite Village is one of the central pineapple areas in Muna Regency. Soil samples were taken using the proportional sampling method on land planted with pineapple plants, at a processing layer depth of 0-30 cm. The soil chemical property parameters analyzed in the laboratory are KTK, pH H2O, C organic, N total, P available, K2O and wet saturation. Determination of soil fertility status is guided by the Soil Research Center. The research results show that the chemical characteristics of the soil in pineapple plantations are soil pH values with slightly acidic to neutral state, low to high C-organic, medium total nitrogen, very high P2O5, low to medium K2O, K2O medium to high KTK and high KB. The soil fertility status is low at location 2, medium at location 2, and high at location 3. The factors inhibiting soil fertility at the research site are low levels of C-organic and K2O.